Story Creation in VIRTUAL GAME WORLDS. - Robertson, Judy; Good, Judith (Communications of the ACM, 2005)
The article discusses how the process of game creation fosters children's programming skills. Much of the research examining games in educational settings looks at children playing games designed by professional software developers, with little focus on children creating their own games. In the case of 3D virtual environment role-playing games, it has required both advanced programming and mathematical skills. However, technology has reached the point where these skills are no longer always necessary: more commercial games are shipping with game-editing tools to encourage skilled members of their user communities to develop further content. With the decreasing focus on programming skills, at least for designing games within a game-creation environment, computer games can be integrated more tightly with specific domains within the curriculum. This article considers the benefits to be gained from enabling children to create stories in the medium of interactive 3D virtual reality computer games. It describes a study in which 10 teenagers created their own stories using the NeverWinter Nights toolset, describing the games creation process, the main findings and their implications.